2016
DOI: 10.1097/ico.0000000000000895
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Clinical Signs and Genetic Characterization of Gelatinous Drop-Like Corneal Dystrophy in a Colombian Family

Abstract: The clinical presentation of GDLD in this family was variable and does not solely support an age-dependent progression of the phenotype, suggesting that environmental or other genetic factors can modify phenotypic expression. The relatively high prevalence of this mutation in the Colombian population suggests that other individuals may have undiagnosed subclinical disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Colombia is classified as an upper‐middle income country, and this study found that genetic tests are available in 42.4% of patients for this group, compared with 96.4% in high‐income countries (Global Retinoblastoma Study Group, Fabian, & Abdallah, 2020). A novel genetic disorder related to TAF1 mutations was described in a Colombian family with a new recognizable hereditary syndrome (O'Rawe, Wu, & Dörfel, 2015), and other manuscripts report cases of oculocutaneous albinism, X‐linked retinoschisis, gelatinous drop‐like corneal dystrophy, and Fabry disease (Mendoza‐Londono, Hiriyanna, & Bingham, 1999; Morantes et al, 2016; Rothstein et al, 2019; Sanabria, Groot, Guzmán, & Lattig, 2012). A case report describes findings in a Colombian family with 9 of 22 members affected by Criswick‐Schepens syndrome (Nicholson & Galvis, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Colombia is classified as an upper‐middle income country, and this study found that genetic tests are available in 42.4% of patients for this group, compared with 96.4% in high‐income countries (Global Retinoblastoma Study Group, Fabian, & Abdallah, 2020). A novel genetic disorder related to TAF1 mutations was described in a Colombian family with a new recognizable hereditary syndrome (O'Rawe, Wu, & Dörfel, 2015), and other manuscripts report cases of oculocutaneous albinism, X‐linked retinoschisis, gelatinous drop‐like corneal dystrophy, and Fabry disease (Mendoza‐Londono, Hiriyanna, & Bingham, 1999; Morantes et al, 2016; Rothstein et al, 2019; Sanabria, Groot, Guzmán, & Lattig, 2012). A case report describes findings in a Colombian family with 9 of 22 members affected by Criswick‐Schepens syndrome (Nicholson & Galvis, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in the third decade, there is secondary stromal opacification and neovascularisation, resulting in severe visual loss. 8 Our patients started to feel their eyesight was impaired since they were in elementary school. Since then, there were no therapy or procedures have been conducted.…”
Section: Discussionmentioning
confidence: 91%